Corporate Power and Responsible Capitalism?: Towards Social Accountability - Jones, Bryn (Edward Elgar Publishing, 2015)
In this important book, Bryn Jones uses insights from political economy, historical analysis and sociological concepts of the corporation, as a socially disembedded but political actor, to address concerns over the over-reach of Anglo-Saxon corporation KM – on page 6: "Following Karl Polanyi, I argue that ST/EM firms have outgrown and threaten to dominate, envelop and even undermine, some of the social and political institutions on which a sustainable market economy depends. Any rebalancing of the relationship between corporations and the rest of society must therefore interrogate the nature of the relationship between market organisations, such as firms, and the social institutions to which they are linked.
Economics; Business Studies
Keywords: ST/EM corporations; business & economics; business ethics; business systems; corporate governance; disembedding; executive managed corporations; industrial management; management; management science; organizational behavior; share-traded corporations; social embedding

Changing employment protection systems : Karl Polanyi's "Double Movement" and the evolution of federal labour standards in Australia 1979 to 2000 - Michelotti, Marco (Association of Industrial Relations Academics of Australia and New Zealand, 2004)
Yes
Management Studies; Business Studies
Keywords: Australia; double movement; industrial relations; labour standards